IMPROVING STUDENTS’ VOCABULARY THROUGH PICTURE CARDS - Wa Saripah (VISION, 2022)
This action research aims to find out if picture is the best work to improve students’ vocabulary at eighth grade (VIII-2) students of MTs Negeri 1 Muna. In this study, the researcher used an action research method which consists of four steps planning action, implementation, observation and reflection. The sample of 29 students were chosen by purposive sampling. The data were collected from observation, questionary and vocabulary test. In analyzing the data, the writer used qualitative and quantitative approach. The finding stressed that picture can help students in gaining vocabulary. This was proved by comparing the result of students’ score in preliminary research to the next cycle. After using picture card for first cycle, the students got 32.57. There was an improvement on students’ vocabulary in the second cycle. They got 55 on average. Another improvement occurred on the third cycle; they gained 81 on average as evidence that they reached the minimum target.